Islamic Educational Values in the Teka Ra Ne'e Tradition of the Kole Community, Bima - Masni, Masni; Tang, Muhammad; Palili, Sampara (Fitrah, 2025)
This research aims to analyze the transformation of Islamic education values contained in the teka ra ne'e tradition in the community of Kole Village, Ambalawi District, Bima Regency. This research uses a qualitative method with an ethnographic approach to trace how these values have changed, adjusted or preserved over time. Data collection techniques were conducted through in-depth interviews, participatory observation, and documentation. The informants consisted of religious leaders, community leaders, and residents implementing the tradition. Data analysis refers to the Miles, Huberman and Saldana model which includes data condensation, data presentation, and conclusion drawing. The results showed that the values of Islamic Education in the teka ra ne'e tradition experienced a transformation in both form and practice, such as the values of worship, care, sincerity, politeness, mutual cooperation, and friendship which are now also influenced by modernization, digitalization, and the developing social system.